If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x) + 4x = 32 Multiply x * x x2 + 4x = 32 Reorder the terms: 4x + x2 = 32 Solving 4x + x2 = 32 Solving for variable 'x'. Reorder the terms: -32 + 4x + x2 = 32 + -32 Combine like terms: 32 + -32 = 0 -32 + 4x + x2 = 0 Factor a trinomial. (-8 + -1x)(4 + -1x) = 0Subproblem 1
Set the factor '(-8 + -1x)' equal to zero and attempt to solve: Simplifying -8 + -1x = 0 Solving -8 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -1x = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -1x = 0 + 8 -1x = 0 + 8 Combine like terms: 0 + 8 = 8 -1x = 8 Divide each side by '-1'. x = -8 Simplifying x = -8Subproblem 2
Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4Solution
x = {-8, 4}
| -3(3+5x)=96 | | 4x^2+4x+1=5 | | -7x^2+14x=y | | 0.18(y-7)+0.04y=0.12y-1.4 | | 4(p)+3(1-p)=3p+7(1-p) | | 0.5v+4.3=2.3 | | -2x-2x-5=5x-2+6 | | 3x^2+12x=y | | (x+4)=5+(5+40) | | v^2+6.1v-6=0 | | 5(4-7x)=405 | | x^2+5x=y | | 9x-4=4x-29 | | 5(p)+6(1-p)=8(p)+3(1-p) | | x-5x+5=13 | | 6(5x+9)=-96 | | 5/7=u/8 | | 25p-12= | | 5(p)+2(1-p)=4(p)+7(1-p) | | -3(y+9)=36 | | -9a^6c^4(5c^3+3a-6)= | | v/9=11/5 | | 2b^2-13b+6=0 | | -4y-y-6=14 | | -7x-2=-30 | | 7/3=9/u | | 0.20x+0.45(50)=33.5 | | A(r)=4(3.14)r^2 | | 4p+3(1-p)=p+7(1-p) | | 25=9+(9x+2) | | -d+46=26 | | 1x+9= |